CLINICAL EXPERIENCE OF USING THE DRUG CELLEX IN PATIENTS WITH VESTIBULAR SYNDROME - Ивонина, Наталья Анатольевна; Петров, Константин Борисович; Филимонов, Сергей Николаевич (Medicine in Kuzbass, 2021)
Chronic cerebral ischemia with predominantly vertebrobasilar insufficiency is a reversible violation of cerebral function caused by a decrease in blood circulation in the vertebral system and the main arteries. Pathology combines various neurological disorders. The leading one is the vestibulo-atactic syndrome, in addition, there are sensorimotor deficits, impaired function of the auditory and visual analyzers in combination with disorders of the cognitive-emotional sphere. A lack of blood flow in IBD leads to a failure of cerebral autoregulation, functional disorders. The lack of oxygen and glucose triggers the mechanisms of oxidative damage to cells, glutamate excitotoxicity, metabolic and energy shifts. For the treatment of patients with vertebrobasilar vascular insufficiency, complex neuroprotective, neurotrophic drugs that reduce the excess of excitatory amino acids, primarily glutamate and aspartate, promote the restoration of local blood flow, as well as provide modulation of neuroplasticity, are promising for use. These characteristics correspond to a tissue-specific protein-peptide complex, which includes more than 1200 signaling proteins and peptides, including growth factors and differentiation of nerve cells and blood vessels-the drug Cellex. This drug has a direct neuropreparative and neurotrophic effect. The aim of this study was to clinically evaluate the effectiveness of the drug Cellex in a group of patients with predominant vestibular syndrome against the background of chronic brain ischemia. The study group consisted of 10 people with chronic vertebrobasilar insufficiency, in whose clinic the vestibular syndrome was the leading one. To objectify clinical manifestations, special tests were conducted for all patients of the study group: the Vertigo Assessment Scale, the Bohannon Standing Stability Test, the MFI-20 Scale of Subjective Assessment of asthenia, the Spielberger Anxiety Scale, cognitive tests: the 5-word Test and the Schulte test. All tests were performed before the start of therapy with Cellex, and after the end of the full course of therapy. The dose of the drug was 0.1 mg/ml, administered subcutaneously, daily, for 10 days. Cellex significantly reduces the intensity of dizziness by SHOCK, improves the stability of standing, reduces the severity of asthenia, reduces the level of situational anxiety, improves the state of cognitive function. The clinical experience of using this drug determines the further study and increase in the number of observed patients with the above pathology in order to obtain more significant and objective results.